Long and short photoperiod buds in hybrid aspen share structural development and expression patterns of marker genes. (5th August 2015) - Rinne, Päivi L.H.; Paul, Laju K.; Vahala, Jorma; Ruonala, Raili; Kangasjärvi, Jaakko; van der Schoot, Christiaan
Highlight: Short photoperiod and apical dominance trigger a shared developmental bud programme at terminal and axillary positions, while the capacity to establish photoperiod-induced dormancy is lost in maturing para-dormant axillary buds. Abstract : Tree architecture develops over time through the collective activity of apical and axillary meristems. Although the capacity of both meristems to form buds is crucial for perennial life, a comparative analysis is lacking. As shown here for hybrid aspen, axillary meristems engage in an elaborate process of axillary bud (AXB) formation, while apical dominance prevents outgrowth of branches. Development ceased when AXBs had formed an embryonic shoot (ES) with a predictable number of embryonic leaves at the bud maturation point (BMP). Under short days, terminal buds (TBs) formed an ES similar to that of AXBs, and both the TB and young AXBs above the BMP established dormancy. Quantitative PCR and in situ hybridizations showed that this shared ability and structural similarity was reflected at the molecular level. TBs and AXBs similarly regulated expression of meristem-specific and bud/branching-related genes, including CENTRORADIALIS-LIKE1 ( CENL1 ), BRANCHED1 ( BRC1 ), BRC2, and the strigolactone biosynthesis gene MORE AXILLARY BRANCHES1 ( MAX1 ). Below the BMP, AXBs maintained high CENL1 expression at the rib meristem, suggesting that it serves to maintain poise for growth. In support of this, decapitation initiated outgrowth of CENL1 -expressing AXBs, but not of dormant AXBs that had switched CENL1 off. This singles out CENL1 as a rib meristem marker for para-dormancy. BRC1 and MAX1 genes, which may counterbalance CENL1, were down-regulated in decapitation-activated AXBs. The results showed that removal of apical dominance shifted AXB gene expression toward that of apices, while developing TBs adopted the expression pattern of para-dormant AXBs. Bud development thus follows a shared developmental pattern at terminal and axillary positions, despite being triggered by short days and apical dominance, respectively.